Aflatoxin contamination of maize, groundnut, and sorghum grown in Burkina Faso, Mali, and Niger and aflatoxin exposure assessment - Falade, Titilayo D.O.; Neya, A.; Bonkoungou, S.; Dagno, K.; Basso, A.; Senghor, A.L.; Atehnkeng, J.; Ortega Beltran, A.; Bandyopadhyay, R. (MDPI, 2022)
Aflatoxin contamination of staple crops by Aspergillus flavus and closely related fungi is common across the Sahel region of Africa. Aflatoxins in maize, groundnut, and sorghum collected at harvest or from farmers’ stores within two weeks of harvest from Burkina Faso, Mali, and Niger were quantified. Thereafter, aflatoxin exposure values were assessed using per capita consumption rates of those crops. Mean aflatoxin concentrations in maize were high, 128, 517, and 659 µg/kg in Mali, Burkina Faso, and Niger, respectively. The estimated probable daily intake (PDI) of aflatoxins from maize ranged from 6 to 69, 29 to 432, and 310 to 2100 ng/kg bw/day in Mali, Burkina Faso, and Niger, respectively. Similarly, mean aflatoxin concentrations in sorghum were high, 76 and 259 µg/kg in Mali and Niger, respectively, with an estimated PDI of 2–133 and 706–2221. For groundnut, mean aflatoxin concentrations were 115, 277, and 628 µg/kg in Mali, Burkina Faso, and Niger, respectively. Aflatoxin exposure values were high with an estimated 9, 28, and 126 liver cancer cases/100,000 persons/year in Mali, Burkina Faso, and Niger, respectively. Several samples were extremely unsafe, exceeding manyfold regulatory levels of diverse countries (up to 2000 times more). Urgent attention is needed across the Sahel for integrated aflatoxin management for public health protection, food and nutrition security, and access to trade opportunities.